Long‐term outcome of hypertensive patients with heart failure with mid‐range ejection fraction: The significance of blood pressure control. Issue 8 (8th July 2019) - Marketou, Maria E.; Maragkoudakis, Spyros; Fragiadakis, Kostantinos; Konstantinou, John; Patrianakos, Alexandros; Kassotakis, Spyridon; Anastasiou, Ioannis; Alevizaki, Afroditi; Kostaki, Artemis; Chlouverakis, Gregory; Vardas, Panos E.; Parthenakis, Fragiskos I.
Abstract: Heart failure (HF) with mid‐range ejection fraction (HFmrEF) is a newly suggested entity in HF. Since it has been inadequately addressed, there is an urgent need to determine the profile of HFmrEF patients and the optimal approach to their management. The present study aimed to assess the long‐term clinical outcomes of hypertensive patients with HFmrEF and the impact of blood pressure (BP) on their mortality and cardiovascular outcome. We performed a retrospective observational study that included 121 hypertensive patients with HFmrEF and 149 hypertensives with heart failure and preserved ejection fraction (HFpEF). The median follow‐up was 84 months (22‐122). Our analysis did not reveal any statistically significant difference between the two groups in total mortality ( P = 0.34) or cardiovascular mortality ( P = 0.54). The total mean survival time was 102.9 months (100.5‐110.1), while the mean survival time was 105.3 months (80.4‐90.2) in HFpEF and 97.6 months (92.7‐102.6) in HFmrEF. An office systolic BP > 139 mm Hg and diastolic BP > 89 mm Hg were significantly associated with both all‐cause mortality ( P = 0.02 and P = 0.013, respectively) and cardiovascular mortality ( P = 0.02 for both). In HFpEF patients, no significant association was found between outcome and office BP. HFpEF and HFmrEF have similar long‐term outcomes. Suboptimal BP levels are a significant risk factor for an adverse outcome in HFmrEF. Our results emphasize the importance of good BP control in order to achieve better outcomes in hypertensives with impaired EF and HF symptomatology.